2019
DOI: 10.1002/ange.201908556
|View full text |Cite
|
Sign up to set email alerts
|

Neutral‐Eosin‐Y‐Photocatalyzed Silane Chlorination Using Dichloromethane

Abstract: Chlorosilanes are versatile reagents in organic synthesis and material science. A mild pathway is now reported for the quantitative conversion of hydrosilanes to silyl chlorides under visible‐light irradiation using neutral eosin Y as a hydrogen‐atom‐transfer photocatalyst and dichloromethane as a chlorinating agent. Stepwise chlorination of di‐ and trihydrosilanes was achieved in a highly selective fashion assisted by continuous‐flow micro‐tubing reactors. The ability to access silyl radicals using photocatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Finally, a reverse hydrogen atom transfer (RHAT) between the IM B and eosin Y-H regenerates ground-state eosin Y and provides the product 2 . In short, the known aspects of the reaction mechanism differ from the reported ones, 9 10 and aerobic oxygen probably plays a crucial role to complete the photoredox cycle by oxidation of the eosin Y excited-state species to the ground state. Although the system is complex, and a precise understanding of the roles of eosin Y awaits further studies, these control experiments also confirm that eosin Y should be critical to both the energy transfer between 3 O 2 with 1 O 2 and the HAT/RHAT steps.…”
Section: Table 1 Survey Of Reaction Conditions ...mentioning
confidence: 75%
See 1 more Smart Citation
“…Finally, a reverse hydrogen atom transfer (RHAT) between the IM B and eosin Y-H regenerates ground-state eosin Y and provides the product 2 . In short, the known aspects of the reaction mechanism differ from the reported ones, 9 10 and aerobic oxygen probably plays a crucial role to complete the photoredox cycle by oxidation of the eosin Y excited-state species to the ground state. Although the system is complex, and a precise understanding of the roles of eosin Y awaits further studies, these control experiments also confirm that eosin Y should be critical to both the energy transfer between 3 O 2 with 1 O 2 and the HAT/RHAT steps.…”
Section: Table 1 Survey Of Reaction Conditions ...mentioning
confidence: 75%
“…In 2019, Wu et al reported visible-light-promoted silane chlorination using dichloromethane in the presence of eosin Y (Scheme 1d ). 10 Through the above works, we serendipitously discovered and developed a previously unknown synthesis of silanols via a visible-light-induced oxidation of tertiary silanes (Scheme 1e ).…”
Section: Table 1 Survey Of Reaction Conditions ...mentioning
confidence: 99%
“…[36] Finally, the resonance at δ = 12 ppm could be assigned to Cl 2 SiEt 2 . [37] The latter signal indicates that ACF could promote the formation of Cl 2 SiEt 2 from ClSiEt 3 .…”
Section: Chemcatchemmentioning
confidence: 99%